2012
DOI: 10.1016/j.nepr.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness of information literacy training for undergraduate midwives to improve their ability to access evidence for practice

Abstract: CitationAn evaluation of the effectiveness of information literacy training for undergraduate midwives to improve their ability to access evidence for practice. 2012, 12 (5) Background: Several authors have suggested that computer skills should be taught within the undergraduate curriculum. In this paper, the focus is mainly on the results of an examination of midwifery students' search strategy in response to a specific question undertaken before and after training session in the first, second and third years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…They found that students who received only one IL session scored lower on their assessments over time than did their counterparts who continued to receive IL sessions through the course of their program. Lalor, Clarke, and Sheaf found that IL training in the first and second years of a midwifery undergraduate program improved post-test scores, but further training in the third year did not contribute to greater knowledge gain [7]. By contrast, Jacobs, Rosenfeld, and Haber, who assessed a program involving IL modules taken throughout the curriculum, found that test scores continually improved with the completion of each module [8].…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that students who received only one IL session scored lower on their assessments over time than did their counterparts who continued to receive IL sessions through the course of their program. Lalor, Clarke, and Sheaf found that IL training in the first and second years of a midwifery undergraduate program improved post-test scores, but further training in the third year did not contribute to greater knowledge gain [7]. By contrast, Jacobs, Rosenfeld, and Haber, who assessed a program involving IL modules taken throughout the curriculum, found that test scores continually improved with the completion of each module [8].…”
Section: Literature Reviewmentioning
confidence: 98%
“…The most common method of evaluation seems to be the use of pre-and posttests [7, 8, 13Á19]. Studies using pre-and post-tests found that there was overall improvement in IL knowledge after students received the training [7,8,13,14,17,19]. In some cases, however, the improvement was found to be marginal [13,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, a three‐year longitudinal study by Lalor et al evaluated midwifery students’ ability to access evidence on a clinical topic after implementing a 16‐hour library‐based intervention. This study also demonstrated that students were successfully able to adopt Pubmed as the primary search tool after their intervention . Our EBM OSCE was unique because it also assessed students’ ability to analyze and communicate their evidence‐based results through the use the outcome measures RR and NNT.…”
Section: Discussionmentioning
confidence: 85%
“…Parallels between the MLA areas of knowledge and those of the public health workforce were demonstrated by Banks and illustrate successful partnerships between health science librarians and public health communities. In Ireland, Lalor has shown how collaboration between faculty and the subject librarian in library based instruction improved undergraduate midwifery students' library research skills . Boyle showed how library collaboration with staff from the School of Nursing, Midwifery and Health Systems enabled the development of an Information Literacy skills programme for the school .…”
Section: Methodsmentioning
confidence: 99%
“…In Ireland, Lalor has shown how collaboration between faculty and the subject librarian in library based instruction improved undergraduate midwifery students' library research skills. 16 Boyle showed how library collaboration with staff from the School of Nursing, Midwifery and Health Systems enabled the development of an Information Literacy skills programme for the school. 17 Collaboration and networking are key to many roles that health librarians take on, and the use of interpersonal skills is essential for effective partnerships.…”
Section: Lis Literature Reviewmentioning
confidence: 99%